Physical Origin of Recurrent Magnetic Dipolarization Events in Saturn's Equatorial Plasma Sheet. Issue 8 (13th August 2021) - Cowley, S. W. H.; Provan, G.
Abstract: We consider the physical origin of reconnection‐related events in Saturn's equatorial current sheet revealed by Cassini, specifically the dipolarization events discussed by Yao et al. (https://doi.org/10.1029/2018JA025837 ) that recur close to the ∼10.7 h planetary period oscillation (PPO) period. We argue that Yao et al.'s preferred recurrence explanation in terms of complete rotations of dipolarized field/current structures around the planet at close to the PPO period is highly implausible. All‐mission observations of ion flows at relevant radial ranges ∼20–30 Saturn radii are essentially invariably sub‐corotational, including reconnection‐related hot ion injections, thus requiring implausible structure propagation at significant speeds through the plasma. We further show their assertion that the nightside events occur at PPO phases unfavorable for reconnection is incorrect. These events instead occur under PPO conditions associated with outward radial plasma displacement and/or a thinning plasma sheet with falling colatitudinal field, shown previously to be optimal for modulated reconnection bursts leading to dipolarizations and plasmoids. We instead suggest these events are related to well‐documented Vasyliunas cycle disturbances, when two reconnection episodes happen to be triggered at similar favorable PPO phases on successive PPO cycles. Yao et al.'s dayside events do occur at phases unfavorable for recurrent reconnection, but may then simply be an effect of periodic field/plasma modulations during the regular PPO cycle combined with subcorotating small‐scale structures often present in the plasma sheet. Both dayside and nightside events can thus be understood within existing knowledge of PPO modulations of the structure and dynamics of Saturn's equatorial current sheet. Key Points: We discuss the physical origin of dipolarization events that recur in Saturn's equatorial current sheet near the planetary rotation period We argue that a proposed picture of long‐lived dipolarized regions rotating around the planet close to this period is highly implausible The events can instead be understood in terms of planetary period oscillation modulation effects on the structure and dynamics of Saturn's equatorial current sheet